The Effect of Anaesthesia Management with Different Fresh Gas Flows on Cognitive Functions of Geriatric Patients: A Randomized Double-blind Study - Bilge Özge Kılıç; Meltem Savran Karadeniz; Emre Şentürk; Meltem Merve Güler; İbrahim Hakan Gürvit; Zerrin Sungur; Ebru Demirel; Kamil Mehmet Tuğrul (Turkish Journal of Anaesthesiology and Reanimation, 2023)

(untitled)
Objective:The present study aimed to compare the effects of two different fresh gas flows (FGFs) (0.5 L min-1 and 2 L min-1) applied during maintenance of anaesthesia on recovery from anaesthesia and early cognitive functions in geriatric patients.Methods:In this prospective, randomised, double-blind study, sixty patients were divided into two groups according to the amount of FGF. Minimal-flow anaesthesia (0.5 L min-1 FGF) was applied to group I and medium-flow anaesthesia (2 L min-1 FGF) was applied to group II during maintenance of anaesthesia. Following the termination of inhalation anaesthesia, recovery times were recorded. The evaluation of cognitive functions was performed using the Addenbrooke’s Cognitive Examination (ACE-R).Results:There was no significant difference between the two groups in terms of demographic characteristics and recovery (P > 0.05). There was no significant difference between the two groups in terms of the preoperative day, the first postoperative day, and the third postoperative day; ACE-R scores (P > 0.05). In group II, on the third postoperative day ACE-R scores were found to be significantly lower than the preoperative ACE-R scores (P=0.04). In group II, third postoperative day ACE-R memory sub-scores (14.53 ± 3.34) were found to be significantly lower than preoperative ACE-R memory sub-scores (15.03 ± 3.57) (P=0.04).Conclusion:In geriatric patients, minimal-flow anaesthesia was not superior to medium-flow anaesthesia in terms of recovery properties and cognitive functions. Keeping in mind that hypoxaemia and changes in anaesthesia levels may occur with the reduction of FGF, both minimal- and medium-flow anaesthesia can be applied with appropriate monitoring without adverse effects on recovery and cognitive functions.